Benthic Foraminifera assemblages in the Kara Sea. - Khusid, Tatyana A (PANGAEA, 1996)
Taxonomic composition and structure of assemblages of the present-day benthic Foraminifera in the Kara Sea has been studied on the base of 37 samples of surface sediments. Three assemblages have been distinguished by composition of dominant species. The assemblage Cribrostomoides subglobosus-Tritaxis nana with prevalence of agglutinating forms, typical for abyssal areas of the World Ocean, occurs in brown oozes in the deep western part of the sea at depths 70-375 m under conditions of considerable bottom stratification. The assemblage Elphidium clavatum-Cassidulina reniforme consists predominantly of species with calcareous shells and is characterized by a wide range of species; this assemblage occurs in the eastern part of the sea at depths 30-90 m in a well-aerated area. Species typical for sublittoral areas of polar regions are dominant. The assemblage Elphidium clavatum-Haynesina orbiculare occupies the littoral estuarine part of the sea. This assemblage is poor in species and not abundant, and it occurs under influence of freshened water masses undersaturated with dissolved carbonaceous matter.
Abundance of benthic Foraminifera in the Kara Sea
Keywords: Archive of Ocean Data; ARCOD; BC; Box corer; DM49; DM49-4377-1; DM49-4380-2; DM49-4381-1; DM49-4381-2; DM49-4382-4; DM49-4383-7; DM49-4383b; DM49-4384-2; DM49-4385-1; DM49-4386-7; DM49-4387-1; DM49-4388-3; DM49-4389-1; DM49-4389-2; DM49-4390-1; DM49-4391-2; DM49-4393-2; DM49-4394-2; DM49-4395-2; DM49-4397-2; DM49-4398-1; DM49-4399-1; DM49-4400-1; DM49-4401-1; DM49-4402-1; Dmitry Mendeleev; GC; Grab; GRAB; Gravity corer; Kara Sea; MULT; Professor Shtokman; PSh12; PSh12-1405; PSh12-1407; SPASIBAIII